Modeling the relationship between infection risk and heart rate variability in elite swimmers - Hellard, P.; Guimaraes, F.; Avalos, M.; Barthelemy, J. C. (Archivos de medicina del deporte, 2008)
Introduction: Elite athletes are exposed to an intense physical and mental stress, caused by competition and intensive training (Gleeson et al., 2007). Effects on immune system might manifest by infections of any type, in particular, muscular diseases and upper respiratory tract infections, which might seriously compromise their training or competitive performance. The immune and nervous systems being connected via the stress neuroendocrine-axis, repercussions on heart rate variability (HRV) are also expected. The objective of this study was to model the relationship between infection risk, physical exercise and HRV in elite swimmers. Methods: This study reports a 4-season longitudinal follow-up of 28 elite swimmers. For each swimmer, infections were weekly reported by medical personnel. HRV test lasted 15 min: 8 min in supine position (SU), 2 min in supine position with control breathing, and 5 min in standing position (ST). Fast Fourier transform was applied to calculate the spectral power. Logistic mixed model methodology was chosen for the analyses because it is able to model binary outcomes with unbalanced data, account for inter-individual variability and adjust for repeated measures. Models related the infection risk to HRV. Results: The main results are: 1/ The infl uence of athletes` levels was highlighted, revealing that risk infection was lower for international compared with national athletes; 2/ A decrease in parasympathetic control in ST increased the risk of infection one week later, during winter; 3/ Muscular diseases were linked to a shift of the autonomic balance in SU toward a decrease in parasympathetic control and an increased in sympathetic drive, during winter. Conclusion: Our results allow for a better understanding of the effect of intensive training on the risk of illness and its association with HRV. Future perspectives for training strategies are proposed.